Методика получения прозрачного препарата удаленного зуба (LLC "Endo Press", 2020)
This article describes a methodology for the preparation of transparent teeth. The teeth were removed after complicated caries. Owing to the way of visualization it is possible to receive the visual three-dimensional image of all root channels system with preservation of all volume of tooth tissues to assess the anatomy of root canals, the fillings quality and evaluation of possible mistakes and complications